Inclusion Properties for Certain Subclasses of Analytic Functions Defined by a Linear Operator. (16th December 2007) - Cho, Nak Eun
Abstract : The purpose of the present paper is to investigate some inclusion properties of certain subclasses of analytic functions associated with a family of linear operators, which are defined by means of the Hadamard product (or convolution). Some integral preserving properties are also considered.